MoS2-coated vertical graphene nanosheet for high-performance rechargeable lithium-ion batteries and hydrogen production - Wang, Ye (2018)
Hybrid nanostructures composed of vertical graphene nanosheet (VGNS) and MoS2 nano-leaves are synthesized by the chemical vapor deposition method followed by a solvothermal process. The unique three-dimensional nanostructures of MoS2/VGNS arranged in a vertically aligned manner can be easily constructed on various substrates, including Ni foam and graphite paper. Compared with MoS2/carbon black, MoS2/VGNS nanocomposites grown on Ni foam exhibit enhanced electrochemical performance as the anode material of lithium-ion batteries, delivering a specific capacity of 1277 mAh g−1 at a current density of 100 mA g−1 and a high first-cycle coulombic efficiency of 76.6%. Moreover, the MoS2/VGNS nanostructures also retain a capacity of 1109 mAh g−1 after 100 cycles at a current density of 200 mA g−1, suggesting excellent cycling stability. In addition, when the MoS2/VGNS nanocomposites grown on graphite paper are applied in the hydrogen evolution reaction, a small Tafel slope of 41.3 mV dec−1 and a large double-layer capacitance of 7.96 mF cm−2 are obtained, which are among the best values achievable by MoS2-based hybrid structures. These results demonstrate the potential applications of MoS2/VGNS hybrid materials for energy conversion and storage and may open up a new avenue for the development of vertically aligned, multifunctional nanoarchitectures.